KEWENANGAN PEMERINTAH DAERAH TERHADAP HAK ULAYAT MASYARAKAT HUKUM ADAT SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 32 TAHUN 2004 - Adonia Ivonne Laturette (SASI, 2011)
The national development faster and rapidly, often requires the state to make the arrangement in all areas including land use that requires people to surrender their land to the State for use for the public interest. Industrial park development, highway construction, agriculture, plantation, mining and so on are some of the basic legitimacy of the state used in the takeover of customary rights of indigenous peoples. With the enactment of Act Number 32 Year 2004 on Regional Autonomy which generally contains the enforcement of the implementation of the handover of authority to the state's right to control local government district or city. In this regard it with the enactment of regional autonomy which is the state's right to control the delegation of authority in the area of land to local governments, local governments should be able to run the authority, especially in the area of land with due regard to the interests of local communities indigenous people themselves in the territory of the Republic of Indonesia